Matching forerunner cities: Climate policy in Turku, Groningen, Rostock, and Potsdam - Kristine Kern; Sam Grönholm; Wolfgang Haupt; Luca Hopman (Review of Policy Research, 2022)
This article analyzes and compares the climate policy and transformation pathways of the forerunner cities Turku (Finland), Groningen (The Netherlands), Rostock, and Potsdam (both located in Germany). Our study combines an international comparison of cities located in three different countries with a national comparison of two German cities. This research design is based on the assumption that national context matters. We argue that the chances for scaling local experiments between cities are particularly high among matching cities, which resemble each other. Such cities have the capability to learn by matchmaking, nationally as well as internationally. All four cities are mid-sized cities of roughly the same size located in advanced democracies in northern and continental Europe. Moreover, within their countries, all four cities have acquired the reputation of being forerunners in the area of climate policy. First, we focus on a comparison of the four cities and identify the strengths and weaknesses of their climate policies. Second, we assess the scaling potential of local experiments, in particular institutional and organizational innovations, integrative and participatory approaches, and leadership. Third, we analyze actual scaling between the two German cities, which share the same national context. More generally, we explore how matching cities can develop from local pioneers to internationally acknowledged leaders, which have the ability to upscale successful local initiatives, nationally as well as internationally.
Keywords: 320; cities; climate policy; experiment; forerunner; scaling; urban transformation; política climática; ciudades; precursor; escalado; experimentar; transformación urbana; 气候政策; 城市; 先行者; 规模化; 实验; 城市转型